2011
DOI: 10.1002/nau.21147
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging following interstim®: An institutional experience with imaging safety and patient satisfaction

Abstract: Although we don't advocate the routine use of MRI following InterStim® implantation, our experience suggests MRI may be feasible under controlled conditions and without adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…Two separate studies have shown that MRI studies of the extremities other than the head and body MRI scanning including the lumbar spine and pelvis can be performed safely with earlier and current InterStim devices. Elkelini 147 as well as Chermanski 161 reported the results from individual small series of patients studied without event using the interstim I device, using 1.5 and 0.6 Tesla machines. In one case, a generator (IPG) was found to be damaged after study due to leaving the magnet switch on, and both studies recommended setting the amplitude to zero and turning the magnet switch off.…”
Section: Mri Consensus Statementmentioning
confidence: 99%
“…Two separate studies have shown that MRI studies of the extremities other than the head and body MRI scanning including the lumbar spine and pelvis can be performed safely with earlier and current InterStim devices. Elkelini 147 as well as Chermanski 161 reported the results from individual small series of patients studied without event using the interstim I device, using 1.5 and 0.6 Tesla machines. In one case, a generator (IPG) was found to be damaged after study due to leaving the magnet switch on, and both studies recommended setting the amplitude to zero and turning the magnet switch off.…”
Section: Mri Consensus Statementmentioning
confidence: 99%
“…The basis for this policy is that potential hazards such as motion, dislocation or torquing of the implanted pulse generator and heating of the leads may occur. However, according to studies based on a few patients, MR imaging with 0.6 or 1.5 Tesla machines may be feasible after Interstim 1 implantation under controlled conditions and without adverse events [31,32].…”
Section: Commentsmentioning
confidence: 99%
“…Although, MRI of the head only may be safely performed under certain circumstances. 34,35 Urinary Diversions and Bladder Augmentations. Patients with intractable detrusor overactivity may be candidates for urinary diversion or physical enlargement of the bladder by augmentation cystoplasty.…”
Section: Bladder Overactivity and Uuimentioning
confidence: 99%